European integration: what lessons for other regions? The case of Latin America - Ettore Dorrucci; Stefano Firpo; Francesco Paolo Mongelli; Marcel Fratzscher (European Central Bank (ECB), 2002)
This paper tests for the hypothesis that institutional integration interacts with economic integration at the regional level. In particular, we ask what lessons can be drawn from the European experience with regional integration for Latin America. Several indicators of institutional and economic integration for both the EU and Latin America are presented. We find that Latin America is currently less economically integrated not only than the European Union today, but in some cases even than the EU at the beginning of its regional integration process. A cluster analysis illustrates that the link between institutional and economic integration has worked both ways throughout the whole EU experience. The more institutional integration went beyond the creation of a customs union and moved towards a common market and an economic and monetary union, the deeper economic integration turned out. Increasing economic integration in turn corroborated and sustained the process of institutional integration.
Keywords: E42; F15; F33; F41; 330; intra-regional exchange rate variability; Regional integration in Europe and Latin America